PENGARUH KARAKTERISTIK PEKERJAAN DAN PEMBERDAYAAN TERHADAP KINERJA PERANGKAT DESA DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA PERANGKAT DESA SE KECAMATAN TLOGOMULYO KABUPATEN TEMANGGUNG) - Andina Diah Rahayu, 11.52.02.0004 (Students Journal of Economic and Management, 2013)
This research aimed to analyze the effect of job characteristics and Empowerment on Job Performance with Organizational Commitment as mediation. Population in this research is 134 person and all of the population being respondents with census methode. Test instruments use validity and reliability, while the model test use R2 test (coefficient of determination), F test (Goodness of Fit) and t-test (t-test). Hypothesis Testing in this research use the regression analysis with t count criteria. Hypothesis testing is used t count frequency distribution test at significance level (Î±) of 5%. The results showed (1) Job Characteristics has positive and significant impact on Organizational Commitment, (2) Empowerment has positive and significant impact on Organizational Commitment, (3) Job Characteristics has positive and significant impact on Job Performance, (4) Empowerment influential positive and significant impact on Job Performance, while (5) The Organizational Commitment does not mediate the effect of Job Characteristics and Empowerment to Job Performance. Â  Keywords: Job Characteristics, Empowerment, Organizational Commitment, and Job Performance